Digital Media for Beginning Reading in Elementary Schools: A Bibliometric Analysis - Eka Kurnia; Diding Bajuri; Devi Afriyuni Yonanda (Journal of Business, Social and Technology, 2026)
Background: With advancements in educational technology and 21st-century literacy demands, research on digital media development for beginning reading instruction in elementary schools has increased. Objective: This bibliometric study aims to trace the trends, publications, and progress of topics in research on the use of digital media in early literacy instruction. Methods: Research data were collected from international scientific databases containing articles on reading literacy, digital media, and elementary education within a specific time frame. A total of 1,436 articles were retrieved from the Scopus database (2010–2025) using standardized search strings and PRISMA-based screening. The analysis was conducted using bibliometric methods with the assistance of scientific mapping software to identify the number of publications, most productive authors, influential journals, as well as collaboration networks and keyword occurrences. Results: The results show a substantial increase in research on reading literacy and digital media over the past decade, with a subsequent surge at its peak after application-based learning technologies, e-books, and interactive multimedia were widely introduced. The most frequently appearing keywords include digital literacy, emergent literacy, interactive reading, and educational technology. Conclusion: This demonstrates that the integration of digital media has become an important focus in supporting early reading skills in elementary school students. Furthermore, the keyword co-occurrence map indicates a strong relationship between the use of digital technology, the development of literacy skills, and innovations in learning methods.